Merkel cells in nevus sebaceus: an immunohistochemical study - Schulz, Tilman; Hartschuh, Wolfgang (The American journal of dermatopathology, 1995)
Nevus sebaceus, considered to be a hamartoma, is known to develop several secondary hyperplastic and neoplastic proliferations. By the use of immunohistochemical studies, we were able to describe a sometimes very striking increase of Merkel cells in nine of 19 nevi sebaccei. Only nevi sebacei that formed follicular germ structures and trichoblastomas showed a Merkel cell hyperplasia. In the hyperplastic epidermis of some cases a slight hyperplasia of singular Merkel cells was observed. In foci with follicular germs and trichoblastomas, however, the Merkel cells were much more abundant and sometimes arranged in cluster. Merkel cell hyperplasia is likely to reprsent another facet of hamartomatous hyperplasia in nevi sebacei. Our observation that trichoblastomas in nevus sebaceus possess, as a rule, hyperplasia of Merkel cells, might be an additional aid to distinguish these tumors from basal cell carcinomas, which are usually devoid of Merkel cells. Furthermore, our findings are a hint that development of follicular germs and trichoblastomas in nevi sebacei may be promoted by Merkel cells.